Effect of serum albumin level on high-dose methotrexate induced toxicities in acute lymphoblastic leukemia patients - Mirza, Mehdi Ali; Aruna, D.; Konatam, Meher Lakshmi (International Journal of Health Sciences, 2023)
Objectives: Methotrexate (MTX) is a key therapeutic agent for leukemias. When given in high doses, leucovorin rescue is added to reduce its toxicity. It has been postulated that low albumin levels are associated with delayed clearance and increased toxicity of MTX. Hence, this prospective cohort study was proposed to evaluate the correlation between serum albumin level and HDMTX toxicity in acute lymphocytic leukemia (ALL) patients and to compare the MTX toxicity in hypo and normoalbuminemic patients. Methods: Forty-six ALL patients of either gender aged 2–40 years receiving HDMTX for 1st time were included in the study. The serum albumin levels were measured before chemotherapy before each cycle. The patients received 24-h infusion of HDMTX on days 8, 22, 36, and 50 (four cycles). The serum concentration of MTX was measured after first cycle only. The patients were followed for toxicities that were graded according to CTCAE-V4.0. Results: There was a negligible correlation between cumulative albumin levels of all four cycles and cumulative toxic events. The median toxic events were 19 (16–23). The Spearmen correlation coefficient ρ was 0.055 (P = 0.460). No association was found between albumin level and MTX toxicity in cycle wise analysis also. In each cycle, there was no significant difference in the toxicities between the hypo and normoalbuminemic patients. Only vomiting showed significant (P < 0.05) inverse correlation with albumin levels. Hypoalbuminemic patients showed significantly (P < 0.01) higher grade of nausea compared to normoalbuminemia. Conclusion: There was negligible correlation between albumin levels and MTX toxicity despite delayed clearance supporting the safety of MTX in mildly hypoabuminemic patients.